Evaluation of two different root-end cavity preparation techniques: A scanning electron microscope study - Aydemir, Seda; Cimilli, Hale; Yoruç, Afife Binnaz Hazar; Kartal, Nevin (European Journal of Dentistry, 2013)
Objective: In this study, we aimed to evaluate and compare the dentinal walls of root-end cavities for the presence of cracks after cavity preparation using US retrotips and Er: YAG laser. Materials and Methods: Fifty single-rooted teeth were prepared by Protaper NiTi rotary system and obturated by lateral condensation. Three milimeters of root-end was resected. Twenty teeth were prepared with US retrotip (Group 1), 20 teeth with Er: YAG laser (Group 2), and 10 teeth without retropreparation (control group). The root-end surfaces were examined under a scanning electron microscope (SEM). Then the cracks of the resected root surfaces were evaluated on microphotographs. Results: No statistically significant difference was detected between US Group and Laser Group for complete, incomplete, intradentinal, and total number of cracks (P = 0.47, P = 0.80, P = 0.69, P = 0.869, respectively). Conclusion: Statistical analysis revealed no significant effect of retropreparation technique on the development of apical cracks (P > 0.05).
Keywords: Er: YAG laser; retropreparation; root-end cavity; ultrasonic retrotips